Doing the truth in love : conversations about God, relationships, and service - Himes, Michael J., 1947- (Paulist Press, 1995)
This basic and engaging theology of God, human relationships and service assists readers in reflecting more faithfully and more theologically on their own lives, particularly if they are involved in pastoral ministry or service projects.